Multi Peran Perempuan: Studi Kasus pada Pedagang Di Tengger - Partisha Sarah Sadilla; Yulianingsih Yulianingsih (Universitas Padjadjaran, 2022)
Gender roles dichotomy generally places women in the domestic area. However, it is common for women to engage in activities that support family income by working in the public sphere; thus they have multiple roles. This study aims to describe the multiple roles among female traders in Tengger. This research was conducted using a qualitative case study model. Data collection was carried out through interviews, observation, and a secondary data collection. This research found that women in Tengger have multiple roles by working in the informal sector such as trading and farming; while at the same they still carry out their role as housewives. This multiple role enables them to master time management skills as well as skills in prioritizing activities.